Ketalization of Glycerol and Acetone to Solketal: Effect of Temperature, Concentration & Mathematical Model - Fikrah Dian Indrawati Sawali; Moh Azhar Afandy; Mega Mustikaningrum; Rara Ayu Lestary (Institut Teknologi Sepuluh Nopember, 2025)
Solketal is a viable method for using glycerol, a by-product of biodiesel production. This study aims to identify the optimal operating parameters for solketal compounds generated from the glycerol ketalization reaction with acetone by using mathematical models that effectively forecast an appropriate framework for this process. This research consists of three critical phases: the ketalization reaction of glycerol with acetone, the characterization of the result solketal products, and the ketalization reaction utilizing the Amberlite IR 120 Na catalyst. The process begins by introducing glycerol and acetone in a mole ratio of 1:3, followed by mechanical Stirring at 500 rpm. The temperature is regulated using a water bath to maintain a constant reaction temperature under specified conditions of 20 °C, 120 °C, 150 °C, and 180 °C, with catalyst masses of 1%, 3%, 5%, and 7%. The mathematical model used is of exponential and polynomial order 2. The findings indicated that the optimal glycerol conversion of 46.01% was attained at 50 °C, using a 5% catalyst concentration throughout a reaction duration of 120 minutes. Second-order polynomial regression is the most appropriate mathematical model to represent this process.